Protocol for a systematic review with meta-analysis and trial sequential analysis of preventive interventions versus any control intervention for parents with a mental disorder on offspring outcomes - Emilie Hestbaek; Jeanne Kofoed; Jane Barlow; Anne Amalie Elgaard Thorup; Michelle Sleed; Sebastian Simonsen; Anna K. Georg; Mette Skovgaard Væver; Sophie Juul (Systematic Reviews)
Abstract Background Offspring of parents with a mental disorder are at high risk of a range of adverse outcomes, highlighting the need for preventive interventions. However, a comprehensive overview of the beneficial and harmful effects of preventive interventions for parents with mental disorders on offspring outcomes are uncertain. The main objective of this systematic review will be to assess the effects of preventive interventions versus any control intervention for parents with a mental disorder on offspring outcomes. Methods/design We will conduct a systematic review with meta-analysis and report it as recommended by Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), bias will be assessed with the Cochrane Risk of Bias tool-version 2 (ROB2), an eight-step procedure will be used to assess if the thresholds for clinical significance are crossed, trial sequential analysis will be conducted to control for random errors, and the certainty of the evidence will be assessed with the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. To identify relevant trials, we will search for published trials in several electronic databases from their inception to the present. We will also search for unpublished trials and grey literature. Two review authors will independently screen the articles, extract data, and perform a risk of bias assessment. We will include any published or unpublished randomized clinical trial comparing a psychological preventive intervention versus any control intervention for parents with any mental disorder. The primary outcomes will be quality of life and incidence of a mental disorder. Secondary outcomes will include internalizing symptoms, externalizing symptoms, serious adverse events, out-of-home placement, and absence from school or daycare. Exploratory outcomes include trauma, socioemotional development, and language development. All outcomes will be assessed in offsping only. Discussion There is an urgent need for a comprehensive, updated systematic review of the beneficial and harmful effects of preventive interventions for children of parents with a mental disorder. The findings of this systematic review are expected to provide evidence-based information for policymakers, clinicians, and researchers to help them make informed decisions about the most effective interventions and guide future research for this highly prevalent population. Systematic review registration PROSPERO CRD42023463421.